THE ROLE OF PRINCIPAL LEADERSHIP IN IMPROVING THE QUALITY OF TEACHING PERSONNEL - Baruno, Yosep Heristyo Endro; Azzahir, Syifak Zainal Abidin; Mustatho; Nuruddin Al-Akbar (STAI Ma'had Aly Al-Hikam Malang, 2025)
This study aims to examine the role, programs, and leadership strategies of principals in improving the quality of educators in Islamic elementary schools (SDI) in Malang City. This study uses a qualitative approach with data collection techniques through interviews, observations, and documentation. Data analysis is carried out by reducing, presenting, and drawing conclusions from the collected data, as well as checking the validity of the data through creativity, transferability, dependability, and confirmability. The results of the study indicate that the role of the principal includes several aspects, namely as an educator, manager, supervisor, administrator, leader, innovator, and motivator. The principal's programs include program formation, assignments, bringing in expert speakers, and conducting further studies and comparative studies. The strategy for developing the quality of educators involves awards, supervision, training, seminars, workshops, and education and training. Supporting factors for principal leadership in improving the quality of educators include high enthusiasm and cooperation, while inhibiting factors are differences in educator character and lack of adequate facilities and infrastructure. This study provides important insights into how principal leadership can improve the quality of educators through various roles, programs, and appropriate strategies as well as the support and challenges faced. Keywords: Leadership; Quality; Educators. Abstrak Penelitian ini bertujuan untuk mengkaji peran, program, dan strategi kepemimpinan kepala sekolah dalam meningkatkan mutu tenaga pendidik di sekolah dasar Islam (SDI) di Kota Malang. Penelitian ini menggunakan pendekatan kualitatif dengan teknik pengumpulan data melalui wawancara, observasi, dan dokumentasi. Analisis data dilakukan dengan mereduksi, menyajikan, dan menarik kesimpulan dari data yang terkumpul, serta melakukan pengecekan keabsahan data melalui credibility, transferability, dependability, dan confirmability. Hasil penelitian menunjukkan bahwa peran kepala sekolah meliputi beberapa aspek, yakni sebagai pendidik, manajer, supervisor, administrator, pemimpin, inovator, dan motivator. Program kepala sekolah antara lain pembentukan program, penugasan, mendatangkan narasumber ahli, serta melaksanakan studi lanjut dan studi banding. Strategi pengembangan mutu pendidik melibatkan penghargaan, supervisi, pelatihan, seminar, workshop, serta pendidikan dan pelatihan. Faktor pendukung kepemimpinan kepala sekolah dalam meningkatkan mutu tenaga pendidik antara lain semangat dan kerjasama yang tinggi, sedangkan faktor penghambatnya adalah perbedaan karakter pendidik dan kurangnya sarana dan prasarana yang memadai. Penelitian ini memberikan wawasan penting tentang bagaimana kepemimpinan kepala sekolah dapat meningkatkan mutu pendidik melalui berbagai peran, program, dan strategi yang tepat serta dukungan dan tantangan yang dihadapi. Kata Kunci: Kepemimpinan; Mutu; Pendidik.